'Best in class' socially responsible investment. The actual performance evaluation between the US and Europe. (3rd April 2022) - Burchi, Alberto; Włodarczyk, Bogdan
ABSTRACT: This study investigates the realized performance of socially responsible investments (SRIs) in US and in European financial markets. We simulate a real investment strategy based on continuous portfolio optimization in the risk-return space. We assume the role of an investor who bases his or her choices on a 'best in class' approach. We evaluate performance using the actual returns achieved by these strategies. Our results show that the socially responsible investor must pay a cost in terms of a lower investment-risk premium according to his or her appetite for risk and geographical area. In the US, SRI investments yield lower returns than non-SRI investments; in Europe, SRI investments yield lower returns and more volatility. Finally, SRIs have greater capacity to reduce risk in terms of both losses and recovery speed.